Variations in seed micromorphology and morphometry of native Indonesian Phalaenopsis and Paphiopedilum orchids - Sucipto Hariyanto (Society for Indonesian Biodiversity, 2019)
Abstract. Hariyanto S. 2019. Variations in seed micromorphology and morphometry of native Indonesian Phalaenopsis and Paphiopedilum orchid. Biodiversitas 20: 3559-3567. Seeds of ten taxa of the genera Phalaenopsis and Paphiopedilum orchids were studied using light and scanning electron microscopy (SEM). Qualitative characters (seed and embryo shape, seed and embryo colour, ornamentation of testa cell, testa cell wall shape) as well as quantitative data (seed and embryo length, seed and embryo width, seed and embryo volume, seed length/seed width, embryo length/embryo width, seed volume/embryo volume and air space) were analysed. Seeds of all studied taxa were fusiform in shape and had smooth testa surfaces. Phalaenopsis testa cells were elongated with cylindrical cell walls, while Paphiopedilum testa cells were polygonal with thin and flat rectangular cell walls. The shape of the embryos was generally ovoid in Phalaenopsis and prolate in Paphiopedilum. Seed colors ranged from brown to dark brown. Embryo colors varied from light yellow, yellowish-brown, dark brown, black and white. Based on our investigation, there are variations in seed and embryo length, seed and embryo width, seed and embryo volume as well as the percentage of the air space, both in Phalaenopsis and Paphiopedilum. In general, the values of seed volume, embryo volume and air space in Paphiopedilum are higher than in Phalaenopsis. Together, the results of the study indicate that morphological and morphometric features can serve to identify live forms and distinguish between species.